Persistent but atypical germinal center reaction among 3rd SARS-CoV-2 vaccination after rituximab exposure - Stefanski, Ana-Luisa; Rincon-Arevalo, Hector; Schrezenmeier, Eva; Karberg, Kirsten; Szelinski, Franziska; Ritter, Jacob; Chen, Yidan; Meisel, Christian; Jahrsdörfer, Bernd; Ludwig, Carolin; Schrezenmeier, Hubert; Lino, Andreia C.; et al. (Frontiers in Immunology, 2022)
Background Durable vaccine-mediated immunity relies on the generation of long-lived plasma cells and memory B cells (MBCs), differentiating upon germinal center (GC) reactions. SARS-CoV-2 mRNA vaccination induces a strong GC response in healthy volunteers (HC), but limited data is available about response longevity upon rituximab treatment. Methods We evaluated humoral and cellular responses upon 3rd vaccination in seven patients with rheumatoid arthritis (RA) who initially mounted anti-spike SARS-CoV-2 IgG antibodies after primary 2x vaccination and got re-exposed to rituximab (RTX) 1-2 months after the second vaccination. Ten patients with RA on other therapies and ten HC represented the control groups. As control for known long-lived induced immunity, we analyzed humoral and cellular tetanus toxoid (TT) immune responses in steady-state. Results After 3rd vaccination, 5/7 seroconverted RTX patients revealed lower anti-SARS-CoV-2 IgG levels but similar neutralizing capacity compared with HC. Antibody levels after 3rd vaccination correlated with values after 2nd vaccination. Despite significant reduction of circulating total and antigen-specific B cells in RTX re-exposed patients, we observed the induction of IgG+ MBCs upon 3rd vaccination. Notably, only RTX treated patients revealed a high amount of IgA+ MBCs before and IgA+ plasmablasts after 3rd vaccination. IgA+ B cells were not part of the steady state TT+ B cell pool. TNF-secretion and generation of effector memory CD4 spike-specific T cells were significantly boosted upon 3rd vaccination. Summary On the basis of pre-existing affinity matured MBCs within primary immunisation, RTX re-exposed patients revealed a persistent but atypical GC immune response accompanied by boosted spike-specific memory CD4 T cells upon SARS-CoV-2 recall vaccination.